A comparison between dexmedetomidine and propofol on extubation times in postoperative adult cardiac surgery patients: a systematic review protocol. (November 2016) - Nguyen, John; Nacpil, Noel
Abstract : Review question/objective: The objective of this systematic review is to synthesize the best available evidence regarding the effects of dexmedetomidine compared to propofol on time to extubation, intensive care unit (ICU) length of stay (LOS), hospital LOS and mortality in postoperative adult cardiac surgery patients. The specific review question is as follows: What is the effectiveness of dexmedetomidine compared to propofol on times to extubation, ICU LOS, hospital LOS and mortality in postoperative adults undergoing cardiac surgery?